Seclusion and its Prevention. (A study on the efforts to release of seclusion and restrain prevention viewed from sociological aspects in Sukoharjo) - Bekti Suharto; Susi Endra Wati; Sr Dayaningsih (Indonesian Journal on Medical Science, 2014)
Abstract: Seclusion is an act putting a block of wood on the hands and/or feet of a person, tied or chained, isolated at a special place in the house or in the woods. Families with mental disorder clients often feel the burden associated with client care. The reason why the family does Seclusion is to prevent the violent behavior, prevent the risk of suicide, and prevent the client's leaving home and family disability to take care for clients of mental disorder.The purpose of this study was to determine the condition of the seclusion client, seclusion client's level of independence and other relationships that affect client toward seclusion and sociological aspects related to the actions or efforts to control seclusion in Sukoharjo in 2013. The study was conducted in two health centers in Sukoharjo using total sampling consist of 15 families, 13 families with client seclusion and 2 families free seclusion clients. After conducting the study, it is expected to achieve a solution to do at the health center or mental health services by the government which in the end it can be achieved ' Sukoharjo free from Seclusion'.Key words: Sociological, Daily Activities, Social Activities